Analyzing the Characteristics of Domestic Wastes in Belik River, the Special Region of Yogyakarta, Indonesia - Slamet Suprayogi; Muh Aris Marfai; Ahmad Cahyadi; Reviana Latifah; Hendy Fatchurohman (ASEAN Journal on Science and Technology for Development, 2019)
The multiplying number of population in the City of Yogyakarta has resulted in a larger volume of wastes in the region. People living on the riverbanks are unfortunately in the habit of discarding domestic waste directly to the river channel, worsening the already polluted water. This study was intended to analyze the characteristics of the municipal wastewater contaminating Belik River. During the water quality test, a rapid investigation method and laboratory analysis were employed. The sampling in the field was based on river segments and travel time of river water. Based on the laboratory test results, the concentrations of phosphate, BOD, and COD in the water bodies had exceeded the standard for Class II water quality indicating pollution due to frequent disposal of household wastes like detergents. The higher the BOD and COD levels, the more unsuitable the water for fisheries and agricultural practices.